In Silico Study of Pyrazolylaminoquinazoline Toxicity by Lazar, Protox, and Admet Predictor - Supandi, Yeni, Fajar Merdekawati (Journal of Applied Pharmaceutical Science, 2018)
Pyrazolylaminoquinazoline is obtained from synthetic AZD4547 and can inhibit kinase activity in recombinant fibroblast growth factor receptor (FGFR) in vitro. The objective of this study was to obtain high activity and low toxicity pyrazolylaminoquinazoline derivatives in silico. The 2-dimensional structures were generated using the ChemDraw application. The Lazar application was used to predict endpoint carcinogenicity, maximum daily dose, and mutagenicity. The ProTox application was used for endpoint LD50 and toxicity classes, while the ADMET application was used for endpoint hepatotoxicity, with reproductive system disorders, and endocrine. Based on the scoring from the three software applications, two compounds were identified as being active against FGFR 2, with no carcinogenic or toxic effects on the liver, endocrine system, and the reproductive system, but they were predicted to have mutagenic effects. These compounds were V29 (N-(5-(3,5-dimethoxy phenethyl -1H-pyrazol-3-yl)-7(octahydro- 2H-pyrido[1,2-a]pyrazine-2-yl) quinazoline-4-amine), with an IC50 of 0.2 ± 0.1 nM and a toxicity score of 1027, and V32 (N-(5-(3,5-dimethoxy phenethyl)-1H-pyrazol-3-yl)-7-(4-(dimethylamino)piperidine-1-yl)quinazoline-4-amine), with an IC50 of 0.3 ± 0.1 nM and a toxicity score of 1024.
Keywords: In silico, Pirazolilaminokuinazoline, Lazar, ProTox, ADMET Predictor.